Mud-to-powder composition and preparation method using multi-element infrared synergistic drying

By employing multi-element infrared synergistic drying technology and precise surface modification, the problems of powder dispersion and stability in mud-to-powder conversion have been solved, achieving efficient dispersion, long-lasting stability, and excellent skin feel for makeup products, thus enhancing the user experience.

CN121015491APending Publication Date: 2025-11-28ZHONGSHAN MEIYUAN COSMETICS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511162160.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-08-19
Publication Date
2025-11-28

AI Technical Summary

Technical Problem

In existing color cosmetic products, the problems of powder dispersion and stability, oil phase compatibility, and the contradiction between anti-settling and usability have not been effectively solved, resulting in problems such as graininess, sedimentation and stratification, and stickiness and heaviness during product use.

Method used

Employing multi-element infrared synergistic drying technology, through precise surface modification and multi-level structural design, components such as myristic acid-modified fluorophlogopite and silane-modified silica are used to form a hydrophobic layer and a three-dimensional network. Combined with gradient pressing and multi-wavelength infrared drying, efficient dispersion of powder and long-term stability of the system are achieved.

Benefits of technology

It achieves efficient dispersion of powder and long-term stability of the system, while taking into account both excellent skin feel and makeup effect, and improves the product's anti-settling performance and user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN121015491A_ABST
    Figure CN121015491A_ABST
Patent Text Reader

Abstract

The invention aims to provide the mud conversion powder composition which is efficient in powder dispersion, long-acting and stable in system and good in skin feeling and makeup effect, and the preparation method of the mud conversion powder composition by utilizing multi-element infrared synergetic drying. The sludge conversion powder composition is prepared from the following components in percentage by mass: 50 to 70 percent of myristic acid modified synthetic fluorophlogopite, 20 to 40 percent of titanium dioxide, 2 to 5 percent of triethoxyoctyl silane modified silicon dioxide, 2 to 5 percent of polymethylsiloxane modified silicon dioxide, 2 to 5 percent of PEG-12 polydimethylsiloxane, 1 to 3 percent of sorbitan isostearate and 1 to 3 percent of diisostearyl malate. The cleaning agent is prepared from the following components in percentage by weight: 1 to 3 percent of polydimethylsiloxane, 0.4 to 1.2 percent of zinc stearate, 0.36 to 0.9 percent of caprylyl glycol, 0.04 to 0.1 percent of ethylhexylglycerin and 0.4 to 1 percent of phenoxyethanol; the preparation method utilizing multi-element infrared synergistic drying is used for preparing the sludge-to-powder composition. The invention is applied to the technical field of cosmetics.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the technical field of cosmetics, and particularly to a mud-to-powder composition and a preparation method using multi-element infrared synergistic drying. Background Technology

[0002] In today's cosmetics market, consumers are placing increasingly stringent demands on the performance and user experience of makeup products. Traditional makeup products, such as pressed powder and liquid foundation, have revealed a series of problems during use.

[0003] Traditional powder-based makeup tends to be dry in texture. While it offers some coverage, its lack of fineness leads to fallout during application, severely impacting the overall look and aesthetics. Furthermore, traditional eyeshadows, due to their loose powder composition, are easily diluted, requiring repeated application and blending with brushes to achieve a noticeable color. This poses a significant challenge for consumers seeking highly saturated stage makeup.

[0004] To meet consumers' higher expectations for makeup products—namely, high coverage, natural and long-lasting finish, good skin adhesion, and convenient user experience—makeup clay-to-powder technology has emerged. As a new form of makeup product, makeup clay-to-powder cleverly combines the advantages of traditional powder and liquid makeup, aiming to solve many of the aforementioned problems existing in current makeup products.

[0005] Although clay-to-powder, as a cosmetic formulation that combines the concealing power of powder with the easy spreadability of liquid, is highly favored in the market, balancing its formulation stability and user experience remains a core technical challenge for the industry. Currently, the stability of clay-to-powder faces three main challenges: First, the dispersion of powder in the oil phase. Due to the polar groups on the original surface of powders such as synthetic fluorophlogopite and titanium dioxide, they are prone to agglomeration due to hydrogen bonding and electrostatic attraction, resulting in a grainy texture or sedimentation and stratification. Second, the compatibility of oil phase components. Oil phase media such as silicone oils and esters of different polarities are prone to phase separation with modified powders and surfactants due to differences in interfacial tension, affecting product uniformity. Third, the contradiction between anti-settling and usability. Traditional methods of achieving stability by simply increasing viscosity often result in a sticky and heavy product when applied, ruining the skin feel.

[0006] Current improvements to powder dispersion often employ single surface modifiers, such as using only fatty acids or silane coupling agents. However, these methods struggle to adapt to complex systems with multiple powder components (such as mica, titanium dioxide, and silica), leading to issues like poor dispersion of some powders. Regarding system stability, while introducing silica to build a network or adding metal soap-based thixotropic agents can address this, the lack of multi-level structural synergy results in an unsatisfactory balance between static anti-settling and dynamic spreadability. Furthermore, some formulations sacrifice makeup effect and skin feel in pursuit of stability; for example, uneven titanium dioxide dispersion reduces concealing power, and improper oil phase combinations can cause stickiness or dryness. Therefore, developing a clay-to-powder formula that achieves efficient powder dispersion, long-term system stability, and excellent skin feel and makeup effect is a pressing technical challenge in this field. Summary of the Invention

[0007] The technical problem to be solved by the present invention is to overcome the shortcomings of the prior art and provide a mud-to-powder composition with efficient powder dispersion, long-term system stability, and excellent skin feel and makeup effect, as well as a preparation method using multi-element infrared synergistic drying.

[0008] The technical solution adopted in this invention is as follows: the high-performance clay powder conversion composition using multi-element infrared synergistic drying comprises the following components by mass percentage: myristic acid-modified synthetic fluorophlogopite 50-70%, titanium dioxide 20-40%, triethoxyoctylsilane-modified silica 2-5%, polymethylsiloxane-modified silica 2-5%, PEG-12 polydimethylsiloxane 2-5%, sorbitan isostearate 1-3%, diisostearyl malate 1-3%, polydimethylsiloxane 1-3%, zinc stearate 0.4-1.2%, octyl glycol 0.36-0.9%, ethylhexylglycerin 0.04-0.1%, and phenoxyethanol 0.4-1%.

[0009] As can be seen from the above scheme, the high proportion of myristic acid-modified fluorophlogopite results in a hydrophobic layer formed by long-chain alkyl groups covering its surface. This reduces sedimentation due to the scaffolding effect of its plate-like structure, while also ensuring good compatibility with the oil phase. The "polar skeleton-hydrophobic chain" structure of sorbitan isostearate is used to aid dispersion and prevent polar agglomeration of the powder. Triethoxyoctylsilane-treated silica introduces "siloxane chains," balancing its interaction with other components and compatibility with the oil phase. Polymethylsiloxane-treated silica, due to its strong hydrophobicity, readily integrates with polymethylsiloxane. The siloxane phases are well-matched, forming a three-dimensional network through intermolecular forces, which enhances the system's viscosity. In the continuous phase, polydimethylsiloxane provides a smooth base, while diisostearyl malate acts as an intermediate polar medium connecting different polar components. PEG-12 polydimethylsiloxane, with its "polyethylene glycol-siloxane chain" structure, serves as an amphiphilic bridge, eliminating interfacial tension differences. Zinc stearate further strengthens the network through hydrophobic interactions and coordination bonds, forming a gel-like state to resist sedimentation upon standing, and exhibiting a rapid decrease in viscosity upon shearing for ease of use. Furthermore, "precise surface modification" achieves polarity matching between the powder and oil phases. Through a multi-level synergistic balance of stability and usability via "particle network + metal soap thixotropy + sheet-like particle scaffolding," while also considering functions such as coverage and skin feel, a highly efficient unity of structure and performance is achieved.

[0010] A preferred embodiment is that the high-performance clay-based powder conversion composition comprises the following specific components by mass percentage: 58.68% myristic acid-modified synthetic fluorophlogopite, 24.45% titanium dioxide, 2.934% triethoxyoctylsilane-modified silica, 2.934% polymethylsiloxane-modified silica, 2.934% PEG-12 polydimethylsiloxane, 1.956% sorbitan isostearate, 1.956% diisostearyl malate, 1.956% polydimethylsiloxane, 0.8% zinc stearate, 0.6% octyl glycol, 0.06% ethylhexylglycerin, and 0.74% phenoxyethanol.

[0011] A preferred embodiment is that the high-performance clay-based powder conversion composition comprises the following specific components by mass percentage: 50% myristic acid-modified synthetic fluorophlogopite, 40% titanium dioxide, 2.5% triethoxyoctylsilane-modified silica, 2.5% polymethylsiloxane-modified silica, 3% PEG-12 polydimethylsiloxane, 2% sorbitan isostearate, 2% diisostearyl malate, 2% polydimethylsiloxane, 1% zinc stearate, 0.6% octyl glycol, 0.06% ethylhexylglycerin, and 0.74% phenoxyethanol.

[0012] A preferred embodiment is that the high-performance clay-based powder conversion composition comprises the following specific components by mass percentage: 70% myristic acid-modified synthetic fluorophlogopite, 20% titanium dioxide, 4.5% triethoxyoctylsilane-modified silica, 4.5% polymethylsiloxane-modified silica, 3% PEG-12 polydimethylsiloxane, 2% sorbitan isostearate, 2% diisostearyl malate, 2% polydimethylsiloxane, 0.6% zinc stearate, 0.06% octyl glycol, 0.74% ethylhexylglycerin, and 0.6% phenoxyethanol.

[0013] The preparation method includes the following specific steps: Step S1: Weigh PEG-12 polydimethylsiloxane, sorbitan isostearate, polydimethylsiloxane, and diisostearyl malate and mix them into a liquid mixture. Heat the liquid mixture to 80-95℃ while stirring it at 200-500r / min for 1-5min until it is completely dissolved and turns milky white. Set the dissolved liquid mixture aside for later use. Step S2: Weigh myristic acid-modified fluorophlogopite, zinc stearate, triethoxyoctylsilane-modified silica, polymethylsiloxane-modified silica, and titanium dioxide and mix them into a powder mixture. Stir at 300-500 r / min for 1-5 min until the mixture is homogeneous. Step S3: Add the powder mixture to the liquid mixture, and then stir the mixed composition several times at 10000-3000r / min, each stirring time is 5-30s until it is evenly mixed. Then weigh octyl glycol, ethylhexylglycerin and phenoxyethanol and add them to the composition. Stir evenly and discharge for later use. Step S4: Vacuum the spare material obtained in step S3 according to the structure of the powder pressing mold and inject it into the powder pressing mold. Use elastic cloth as the powder pressing medium and press it at least twice with a pressure of 80±20kg / cm² to obtain the filled material. Step S5: Place the aluminum tray filled with material into the heating area of ​​the infrared radiation heater, start the infrared radiation heater, set the infrared wavelength range to 5-1000μm and the power to 1000-1500W, and set the drying time according to the thickness of the billet for drying. Step S6: After drying is complete, remove the solidified material to obtain a high-performance clay-based powder composition.

[0014] As can be seen from the above scheme, the liquid mixture, i.e., the oil phase, adopts a temperature-controlled-shear synergistic pretreatment. This process achieves shearing by controlling temperature and stirring, thereby breaking the interfacial tension of the oil phase and promoting the formation of a stable miscible system between siloxane chains with large polarity differences and ester molecules, providing a uniform medium substrate for subsequent powder dispersion. The premixing of the powder system involves mutual collision and stirring shearing between powder particles to initially break up agglomerates (especially the primary polar agglomerates of titanium dioxide). Simultaneously, the steric hindrance effect of the mica sheet structure is utilized to reserve dispersion channels for subsequent fusion with the oil phase, reducing energy consumption and agglomeration risk during high-speed mixing. The molecular-level bonding of the powder and oil phase employs a step-by-step high-speed shearing process. The strong shearing force generated by the high rotation speed tears apart the weak bonds remaining on the powder surface (such as hydrogen bonds and van der Waals forces), prompting oil phase molecules to rapidly encapsulate the modified layer on the powder surface (such as the long-chain alkyl and siloxane chains of myristic acid), forming a "powder-oil phase" core-shell structure. The pulse interval design with multiple stirring cycles avoids the temperature rise of the system caused by continuous shearing (preventing silicone oil volatilization or ester oxidation). During pressing and molding, stress gradient transfer promotes the directional alignment of powder particles (mica sheet-like structures parallel to the surface, enhancing uniform coverage), while simultaneously promoting the uniform distribution of the oil phase between particles. This ultimately yields a compact structure with a density ≥1.2 g / cm³ and no pores, significantly improving the product's resistance to sedimentation and weathering. Finally, curing employs multi-wavelength infrared synergy, not simple radiation of a single wavelength, but a broad spectral radiation range of 5-1000 μm specifically designed based on the molecular structural characteristics of the material components, achieving precise heating of different components in the system. Among them, the 5-20μm short-wavelength infrared mainly acts on small molecule components in the oil phase (such as polydimethylsiloxane and diisostearyl malate), accelerating diffusion by exciting their molecular chain vibrations and promoting the uniform distribution of the oil phase in the gaps between powder particles; the 50-200μm mid-wavelength infrared can penetrate to the middle layer of the green body and act on surface-modified powders (such as myristic acid-treated synthetic fluorophlogopite and triethoxyoctylsilane-modified silica), causing the long-chain alkyl and siloxane chains on the powder surface to form stronger hydrophobic interactions with the surrounding oil phase molecules, thus strengthening the "powder-oil phase" interface bonding; the 800-1000μm long-wavelength infrared penetrates deep into the core of the green body and acts on thixotropic agents such as zinc stearate, converting molecular vibrational energy into heat energy, promoting the formation of coordination bonds between zinc ions and residual polar sites on the powder surface, further stabilizing the three-dimensional network structure.

[0015] A preferred embodiment is that after the set drying time is reached in step S5, the power supply of the infrared radiation heater is turned off, and the heater is left to cool for a certain period of time before being taken out. Attached Figure Description

[0016] Figure 1 This is a physical product image of the clay-based high-performance powder conversion composition. Detailed Implementation

[0017] The high-performance clay powder conversion composition utilizing multi-element infrared synergistic drying comprises the following components by mass percentage: 50-70% myristic acid-modified synthetic fluorophlogopite, 20-40% titanium dioxide, 2-5% triethoxyoctylsilane-modified silica, 2-5% polymethylsiloxane-modified silica, 2-5% PEG-12 polydimethylsiloxane, 1-3% sorbitan isostearate, 1-3% diisostearyl malate, 1-3% polydimethylsiloxane, 0.4-1.2% zinc stearate, 0.36-0.9% octyl glycol, 0.04-0.1% ethylhexylglycerin, and 0.4-1% phenoxyethanol.

[0018] Myristic acid-modified fluorophlogopite accounts for 50-70% of the composition, which makes the surface of the composition covered by the long-chain alkyl group of myristic acid to form a hydrophobic layer. It is well compatible with the oil phase, and the plate-like structure reduces sedimentation through the "scaffolding effect", providing a stable skeleton for the composition system while giving it a silky texture.

[0019] Titanium dioxide accounts for 20-40% and mainly provides coverage. It is dispersed with the help of sorbitan isostearate. Its "sorbitan polar skeleton" is adsorbed on the surface of titanium dioxide, and the "isostearate hydrophobic chain" extends into the oil phase to avoid polar aggregation and ensure an even makeup effect.

[0020] Triethoxyoctylsilane-modified silica and silicone oil-modified silica each comprise 2-5%. Triethoxyoctylsilane-modified silica introduces "siloxane chains," which retain a small number of polar sites to interact with other components, while also being compatible with the oil phase through hydrophobic chains, thus acting as a "bridging agent" to promote the dispersion of different powders. The surface of polymethylsiloxane-modified silica is covered with polydimethylsiloxane chains, and its strong hydrophobicity makes it highly compatible with polydimethylsiloxane in the system. The two types of silica can form a three-dimensional network structure through intermolecular forces, enhancing the viscosity of the system to resist sedimentation.

[0021] PEG-12 polydimethylsiloxane, comprising 2-5%, contains both polyethylene glycol (polar) and siloxane chains (hydrophobic), acting as an amphiphilic bridge. One end binds to a slightly more polar component, while the other end is compatible with the silicone oil phase, eliminating interfacial tension differences and promoting system compatibility. Sorbitan isostearate, comprising 1-3%, acts as a surfactant to aid in the dispersion of powders such as titanium dioxide. Its structural characteristics help solve the problem of powder agglomeration caused by polarity. Isostearyl malate, comprising 1-3%, is an ester oil with moderate polarity, acting as an intermediate polar medium to connect low-polarity silicone oil with slightly higher polarity components, preventing phase separation. Polydimethylsiloxane, comprising 1-3%, serves as the main continuous phase, providing a smooth substrate, exhibiting good compatibility with hydrophobically treated powders, and synergistically acting with other siloxane components.

[0022] Zinc stearate, accounting for 0.4-1.2%, is a typical oil-phase thixotropic agent. Its long stearic acid chain can combine with the alkyl chain on the powder surface through hydrophobic interaction, and zinc ions form coordination bonds with residual polar sites on the powder surface, further enhancing the network. When standing, it forms a gel state to resist sedimentation, and its viscosity drops sharply during shearing, making it easy to use, thus balancing stability and usability. Octyl glycol 0.36-0.9%, ethylhexylglycerin 0.04-0.1%, and phenoxyethanol 0.4-1% work together as preservatives to inhibit microbial growth and ensure the stability of the formulation system through synergistic effects. The proportions of each ingredient are precisely adjusted. The high proportion of myristic acid-modified synthetic fluorophlogopite ensures the basic stability and texture of the system, while the proportion of titanium dioxide ensures the coverage effect. The combination of various additives and powders works synergistically in terms of dispersion, compatibility, and anti-settling, so that the composition can be stabilized in the clay-to-powder process, while taking into account both good skin feel and makeup effect.

[0023] The preparation method includes the following specific steps: Step S1: Weigh PEG-12 polydimethylsiloxane, sorbitan isostearate, polydimethylsiloxane, and diisostearyl malate and mix them into a liquid mixture. Heat the liquid mixture to 80-95℃. While heating, stir the liquid mixture at a linearly varying speed of 200-500r / min for 1-5min until it is completely dissolved and turns milky white. Set aside the dissolved liquid mixture for later use. Step S2: Weigh myristic acid-modified fluorophlogopite, zinc stearate, triethoxyoctylsilane-modified silica, polymethylsiloxane-modified silica, and titanium dioxide and mix them into a powder mixture. Stir the mixture for 1-5 minutes at a linearly varying speed of 300-500 r / min until it is uniform. The polymethylsiloxane-modified silica is in the form of spherical particles. Step S3: Add the powder mixture to the liquid mixture, and then stir the mixed composition twice at a linearly varying speed of 10000-3000r / min, with an interval between the two stirrings. Each stirring time is 5-30s until the mixture is uniform. Then weigh octyl glycol, ethylhexylglycerin, and phenoxyethanol and add them to the composition. Stir until uniform and discharge for later use. Step S4: Vacuum the spare material obtained in step S3 according to the structure of the powder pressing mold and inject it into the powder pressing mold. Use elastic cloth as the powder pressing medium and press it at least twice with a pressure of 80±20kg / cm² to obtain the filled material. Step S5: Place the aluminum tray filled with material into the heating area of ​​the infrared radiation heater, start the infrared radiation heater, and perform multi-wavelength heating with an infrared wavelength range of 5-1000μm and a power of 1000-1500W. Set the drying time according to the thickness of the billet and dry it. After the set drying time is reached, turn off the power of the infrared radiation heater and let it stand for a certain period of time to cool. For thick billets, set a step-by-step power parameter that changes with time, and monitor the surface temperature of the aluminum tray and the internal temperature of the billet in real time to ensure uniform temperature and consistent drying of the material. Step S6: After drying is complete, remove the cured material, such as... Figure 1 As shown, a high-performance clay-based powder conversion composition was obtained.

[0024] To verify the effect of component ratio on the mud-to-powder conversion performance, three sets of examples were set at the boundary and median of the formulation range for key components (myristic acid-modified synthetic fluorophlogopite, titanium dioxide, triethoxyoctylsilane-modified silica, silicone oil-modified silica, and zinc stearate). The preparation methods strictly followed the document steps (heating temperature 80-95℃, pressing pressure 80±20kg / cm², drying time 5-20min). The optimal solution was compared by indicators such as stability, skin feel, and makeup effect.

[0025] Example 1: In this embodiment, the composition of the high-performance clay-based powder conversion composition is shown in Table 1 below.

[0026] Table 1. Components and their mass percentages contained in Example 1.

[0027] Example 2: In this embodiment, the composition of the high-performance clay-to-pulverizer composition is shown in Table 2 below.

[0028] Table 2. Components and their mass percentages included in Example 2.

[0029] Example 3: In this embodiment, the composition of the high-performance clay-based powder conversion composition is shown in Table 3 below.

[0030] Table 3. Components and their mass percentages contained in Example 3.

[0031] Comparative Example 1: Table 4. Components and their mass percentage in ordinary dry powder.

[0032] Comparative Example 2: Table 5. Components and their mass percentage in traditional liquid powders.

[0033] Comparative Example 3: Table 6. Ingredients and their mass percentage in traditional mashed potatoes.

[0034] Performance test comparison results: Table 7. Performance test comparison results of Examples 1 to 3 and Comparative Examples 1 to 3.

[0035]

[0036] In Example 1, the ratio of myristic acid-modified fluorophlogopite to titanium dioxide is balanced. This balance ensures system stability through the "scaffolding effect" of mica (no oil separation during high-temperature storage, no particle feel during low-temperature cycling), while sorbitan isostearate fully disperses titanium dioxide, achieving uniform coverage. Triethoxyoctylsilane / polymethylsiloxane-modified silica forms a three-dimensional network, which, combined with zinc stearate, balances static stability and dynamic spreadability. After 8 hours, there is no makeup fading or creasing, and the skin feel is non-sticky, demonstrating optimal overall performance. Example 2's advantage is its outstanding coverage, meeting high-coverage needs. Example 3's advantages are excellent stability (no morphological change under both high and low temperature environments) and a silky, non-sticky skin feel.

[0037] Comparative Example 1 uses synthetic mica and talc as the main fillers, and is made by simple mixing and pressing. Although there is no obvious change in morphology during high / low temperature storage (solid physical stability), due to the lack of surface modification and multi-level structural design, the oil phase and powder phase are not well integrated, resulting in a noticeable dry feeling when applied. Moreover, the loose powder leads to significant makeup removal after 8 hours, powder accumulation and creasing, and poor coverage evenness. Its overall performance is significantly different from Example 1. Comparative Example 2 contains synthetic fluorophlogopite and sericite, but does not use precise surface modification technology. A small amount of oil droplets are released on the surface during high-temperature storage, and the texture thickens and clumps easily during low-temperature cycling. After 8 hours, the T-zone experiences severe makeup removal, and the coverage is patchy even with large areas. The overall stability and makeup lasting effect are not as good as Example 1. Comparative Example 3 contains a high proportion of polydimethylsiloxane and isononyl isononyl ester. When stored at high temperatures, a large amount of oil seeps out and clumps at the bottom. When circulated at low temperatures, the texture becomes soft and difficult to spread, resulting in a strong sticky feeling. After 8 hours, the makeup is almost ruined, and the concealing power is poor. In terms of stability, skin feel, and makeup effect, it is far inferior to the embodiment of the present invention.

[0038] In summary, Example 1 achieved the optimal balance of "stability, skin feel, and makeup effect" through precise control of the formula ratio and synergistic process.

[0039] This invention addresses three core pain points that have long existed in the field of clay-to-powder conversion of cosmetics: "difficulty in powder dispersion, poor system stability, and imbalance between skin feel and makeup effect." Through the deep integration of materials science and process technology, it has constructed an innovative solution with "precise surface modification, multi-level structural synergy, and high-efficiency infrared curing" as its core, achieving a breakthrough in the entire chain of technology from clay-to-powder conversion from formula design to industrial production.

[0040] The core principle lies in breaking through the performance constraints of traditional mud-to-powder conversion through multi-dimensional intermolecular forces and structural design: precise adaptation of surface modification—using myristic acid to modify and synthesize fluorophlogopite to construct a hydrophobic plate-like framework, its long-chain alkyl capping layer achieves high compatibility with the oil phase, while inhibiting sedimentation through the "scaffolding effect"; silica modified by triethoxyoctylsilane and polymethylsiloxane respectively forms a composite particle network of "polar bridging-strong hydrophobic synergy", which not only solves the dispersion contradiction of multi-component powders (mica, titanium dioxide, silica), but also enhances the viscosity of the system through intermolecular forces. The dynamic equilibrium of multi-level structure—zinc stearate, as an oil-phase thixotropic agent, strengthens the three-dimensional network through hydrophobic interactions and coordination bonds. When stationary, it forms a gel state to resist sedimentation, and when sheared, its viscosity drops sharply to achieve easy extensibility, perfectly balancing "static stability" and "dynamic usability"; PEG-12 polydimethylsiloxane and diisostearyl malate form an "amphiphilic bridge-intermediate polar medium" system, eliminating the difference in interfacial tension between the oil phase and solving the compatibility problem.

[0041] In terms of structural design, the composition achieves functional synergy through precise control of component ratios: a high proportion of myristic acid-modified synthetic fluorophlogopite lays the foundation for a silky skin feel and a stable base, titanium dioxide ensures concealing power, two types of modified silica and zinc stearate construct a multi-level stable network, and with the polarity matching of siloxane and ester components, a three-in-one formulation system of "coverage-stability-skin feel" is formed.

[0042] At the process level, the synergistic process of "gradient pressing (80±20kg / cm²) + vacuum injection" forms a key support: the vacuum environment effectively eliminates residual air bubbles during the material injection process, and the stress buffering effect of the elastic cloth medium, combined with the step-by-step pressure transmission, promotes the directional arrangement of powder particles (especially the parallel distribution of mica sheet-like structures) and uniform filling of the oil phase, which not only ensures the compact density of the green body ≥1.2g / cm³, but also reduces the risk of morphological defects such as cracking and color bleeding; among them, gradient pressing is to apply linearly varying pressure within the pressure value range.

[0043] The core breakthrough of this invention's process system lies in its multi-element infrared synergistic drying technology. Through precise control of a 5-1000μm wide spectrum and 1000-1500W power, it achieves "targeted solidification" of the mud-to-powder green body. Compared to traditional hot air drying, this technology improves drying efficiency by over 40% by matching wavelength with the molecular vibration characteristics of the material components. Short-wavelength infrared promotes uniform diffusion of the oil phase, mid-wavelength infrared strengthens the powder-oil phase interface bonding, and long-wavelength infrared stabilizes the three-dimensional network. The synergistic effect of these three elements increases the uniformity of the green body's density to over 95%. Testing shows that products using this infrared technology exhibit 30% better anti-settling performance than those using traditional processes, and the agglomeration rate after low-temperature cycling is controlled below 0.5%.

[0044] In summary, this invention not only provides a replicable "formula-process" solution for mud-to-powder technology, but also achieves a balance of all elements in cosmetics through a multi-dimensional synergistic stabilization mechanism and an efficient infrared drying curing path. Specifically, the multi-element infrared synergistic drying technology uses a 5-1000μm wide spectrum to achieve precise targeted heating. Short wavelengths accelerate oil phase diffusion, medium wavelengths strengthen interface bonding, and long wavelengths stabilize the three-dimensional network, solving the problem of external dryness and internal moisture in traditional hot air drying, thus achieving a uniform density of over 95% in the blank. Power adjustment of 1000-1500W adapts to different blank thicknesses of 0.5-2cm, and step-by-step temperature adjustment avoids uneven shrinkage, while controlling the temperature at ≤95℃ to prevent component oxidation. Compared to traditional processes, drying efficiency is improved by more than 40%, ensuring skin feel and makeup effect while providing an efficient and controllable solution for mass production, and can be applied to various types of cosmetics.

[0045] Although the embodiments of the present invention are described with reference to actual solutions, they do not constitute a limitation on the meaning of the present invention. Modifications to the embodiments and combinations with other solutions based on this specification will be obvious to those skilled in the art.

Claims

1. A mud-to-powder composition, characterized in that, It comprises the following components: myristic acid treated synthetic fluorphlogopite 50-70%, titanium dioxide 20-40%, triethoxysiloxy modified silicon dioxide 2-5%, polymethylsiloxane modified silicon dioxide 2-5%, PEG-12 dimethicone 2-5%, sorbitan isostearate 1-3%, diisostearyl malate 1-3%, dimethicone 1-3%, zinc stearate 0.4-1.2%, octisalate 0.36-0.9%, ethylhexylglycerin 0.04-0.1%, phenoxyethanol 0.4-1%.

2. The mud-to-powder composition of claim 1, wherein, It comprises the following specific components: myristic acid treated synthetic fluorphlogopite 58.68%, titanium dioxide 24.45%, triethoxysiloxy modified silicon dioxide 2.934%, polymethylsiloxane modified silicon dioxide 2.934%, PEG-12 dimethicone 2.934%, sorbitan isostearate 1.956%, diisostearyl malate 1.956%, dimethicone 1.956%, zinc stearate 0.8%, octisalate 0.6%, ethylhexylglycerin 0.06%, phenoxyethanol 0.74%.

3. The mud-to-powder composition of claim 1, wherein, It comprises the following specific components: myristic acid treated synthetic fluorphlogopite 50%, titanium dioxide 40%, triethoxysiloxy modified silicon dioxide 2.5%, polymethylsiloxane modified silicon dioxide 2.5%, PEG-12 dimethicone 3%, sorbitan isostearate 2%, diisostearyl malate 2%, dimethicone 2%, zinc stearate 1%, octisalate 0.6%, ethylhexylglycerin 0.06%, phenoxyethanol 0.74%.

4. The mud-to-powder composition of claim 1, wherein, It comprises the following specific components: myristic acid treated synthetic fluorphlogopite 70%, titanium dioxide 20%, triethoxysiloxy modified silicon dioxide 4.5%, polymethylsiloxane modified silicon dioxide 4.5%, PEG-12 dimethicone 3%, sorbitan isostearate 2%, diisostearyl malate 2%, dimethicone 2%, zinc stearate 0.6%, octisalate 0.06%, ethylhexylglycerin 0.74%, phenoxyethanol 0.6%.

5. A process for the preparation of a mud-to-powder composition according to any one of claims 1 to 4, by multivariate infrared synergistic drying, characterized in that, It comprises the following specific steps: Step S1, weigh PEG-12 dimethicone, sorbitan isostearate, dimethicone, diisostearyl malate and mix into a liquid mixture, heat the liquid mixture, the heating temperature is 80-95℃, while heating, stir the liquid mixture at 200-500r / min for 1-5min, until completely dissolved and milky white, the dissolved liquid mixture is left for standby; Step S2, weigh myristic acid treated synthetic fluorphlogopite, zinc stearate, triethoxysiloxy modified silicon dioxide, polymethylsiloxane modified silicon dioxide, titanium dioxide and mix into a powder mixture, and stir at 300-500r / min for 1-5min, until uniform stirring; Step S3, the powder mixture is added to the liquid mixture, then the mixed composition is stirred at 10000-3000 r / min for several times, each time for 5-30 s to mix evenly, then the capryl glycol, ethylhexyl glycerin, phenoxyethanol are weighed and added to the composition, stirred evenly and discharged for standby; Step S4: the standby material body obtained in step S3 is vacuumized according to the structure of the powder pressing mold and injected into the powder pressing mold, with elastic cloth as the powder pressing medium, and pressed at least twice at a pressure of 80±20 kg / cm² to obtain a filled material body; Step S5: the aluminum disc with the filled material body is placed in the heating area of the infrared radiation heater, the infrared radiation heater is started, the infrared wavelength range is set to 5-1000 μm, the power is set to 1000-1500 W, and the drying time is set according to the thickness of the blank for drying; Step S6: after drying is completed, the solidified material body is taken out to obtain a high-performance powder composition with clay.

6. The method of claim 5, wherein: After the set drying time in step S5 is reached, the power of the infrared radiation heater is turned off, and the material body is cooled for a certain period of time before being taken out.